Analisis Sistem Pengendalian Intern atas Pengeluaran Kas Pada BMT AL Muhsin Di Kota Metro - Arrasyid, Rois Ikhsan (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to find out how the internal control system for cash disbursements at the Metro City State Electricity Company. This research is qualitative in nature and uses a descriptive analysis approach. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results showed that the internal control system implemented by BMT. Metro City is good. This is because BMT AL Muhsin Kota Metro has implemented an internal control system based on standard operating procedures (SOP). This is proven by the fact that in the company's internal cash control there are parties involved, documents and contents of cash evidence involved both in the system of cash receipts and cash disbursements.